The Psychology Of Educational Aids And Their Impact On Teaching The Arabic Language To Non-Native Speakers/ سيكولوجية الوسائل التعليمية وأثرها في تعليم اللغة العربية للناطقين بغيرها - Abdullah, Erfan Abdeldaym; Salem Alawadi, Elsayed Mohamed; bin Masman, Haji Muhammad; Mahdi, Rijal (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This research emphasizes the overlooked importance of educational resources in Arabic language teaching for non-native speakers. It highlights the risks of choosing resources that do not align with students' preferences; the psychological impact of instructional materials on students' learning experiences is underscored by a call for building resources on psychological foundations for maximum effectiveness. The research employs a quantitative methodology. The survey, consisting of quantitative and qualitative questions, is administered to education practitioners and specialists. The study follows a descriptive method of data collection and analysis, emphasizing the quantitative aspects of the survey while also including qualitative insights from participants. Results have demonstrated the positive influence of educational materials on student performance. However, the psychological impact requires further investigation in teaching Arabic to non-native speaker.